ARAHAN REHABILITASI LAHAN PASCA TAMBANG TIMAH UNTUK PENGEMBANGAN WILAYAH DI KABUPATEN BANGKA SELATAN - Fahri Setiawan; Kukuh Murtilaksono; W Widiatmaka (TATALOKA, 2019)
Tin Mining raised economic people in South Bangka regency, however mining produced marginal land and was be must be fixed. The research aimed to arrange a direction of rehabilitation post-mine-tin land of environmental, economic, and social aspects for regional development in Bangka Selatan regency. Methods using were on-screen digitation, forestry ministerial rule 60th the year 2009, NPV, BCR, IRR, interview, AHP, TOPSIS, and GDP. Post-mine-tin land in the cultivation area was 11,224.8 hectares. Based on the assessment of forestry ministry rule 60th year 2009 score of oil palm was 72, and the rubber was 71.96. NPV, BCR, and IRR score of oil palm were Rp. 425,629,907.13, 2.83 and 44%, while rubber were Rp. 23,440,706.38, 1.19, and 11%. Rubber was selected by 12 stakeholders, while oil palm was two stakeholders. Based on TOPSIS, the rehabilitation plant was oil palm. District of Tukak Sadai (0.56), Toboali (0.52), and Air Gegas (0.51) were a category of very priority. District of Payung (0.44) and Simpang Rimba (0.40) were a priority. The District of Pulau Besar (0.32) was a moderate priority. District of Lepar Pongok (0.13) was a low priority, and a district of pongok islands (0.0) was a very low priority for rehabilitation. The estimated GDP per year of oil palm was Rp. 501,824,095,033.34.